Innovation and Tacit Knowledge - Kaur, Arvinder; Singh, Hardeep (Prabandhan: Indian Journal of Management, 2010)
Innovation refers to finding new and better ways of doing existing tasks by converting new knowledge into new products and services. The new knowledge can be technical or market related. Technical knowledge refers to the inputs like components, process, and know-how that contribute to output. Market knowledge means the innovative /new designs, presentation techniques, distribution and customer service methods as well as new forms of differentiation, positioning and advertising. Knowledge, on the other hand, is defined by Davenport and Prusak as, "A fluid mix of framed experiences, values, contextual information and expert insight that provides a framework for evaluating and incorporating new experiences and information." It is not by chance only that knowledge is used so heavily in the description of innovation.